ANALISIS PENENTUAN HARGA POKOK PRODUKSI UDANG VANAME (STUDI KASUS PETAMBAK GAMPONG PALONG KECAMATAN GLUMPANG BARO KABUPATEN PIDIE) - Sundari, Sundari; Bustamam, Bustamam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study had a purposed to evaluate the determination cost production of Vanname Shrimp in Gampong Palong. This study used descriptive qualitative method with sample choosed by primary data. The results of this study indicate that the price with cost on pricing method in a full costing approach didnt showed the higher result than the factory, namely Rp 52.652 per kg. where the shrimp cost in order the theor that existed. However, it is not a basic determined the price because the price didnt resemble the theory that pond farmersonly take into account price of shrimp based on the market.